Criminology Review of the Crime of Child Trafficking for the Purpose of Prostitution - Simatupang, Rajarif Syah akbar (Inspiring Law Journal, 2022)
Based on the results of the study, it was stated that the causes of the crime of trafficking in children for the purpose of prostitution were poverty (economic) factors and non-existent or inadequate employment opportunities. Legal protection for child victims of child trafficking for the purpose of prostitution can be done in various ways, including through rehabilitation efforts, efforts to protect from identity reporting through mass media and to avoid labeling, providing safety guarantees, receiving assistance or advocacy during the case process and afterward. as well as providing accessibility to obtain information on case developments. Factors affecting the legal protection of child victims of the crime of trafficking in children for the purpose of prostitution are in terms of legislation due to the weakness factor of the law itself in ensnaring perpetrators of criminal acts of trafficking in children and the threat of punishment is still relatively light. Another thing is also because there is no law that specifically regulates the problem of child trafficking, the indifference of the people themselves who tend to be ignorant in seeing the phenomenon of child trafficking, in addition there are also a small number of people who turn out to legalize their children to become prostitutes in order to help the family economy